The Development of Computer-Based Test (CBT) Based on Hypertext Preprocessor (PHP) - Baharuddin J.H.; Indri Astuti; Aloysius Mering (STKIP Singkawang, 2020)
This study aims to produce design, to know the profile and to determine the level of effectiveness of the Hypertext Preprocessor (PHP) based on Computer-Based Test (CBT) to Test of English For Academic Proficiency (TEAP) IKIP PGRI Pontianak. The development research method is the ADDIE development design model. The research subjects were students of the eighth semester English study program and the lecturers and staff who served at UPT Bahasa of IKIP PGRI Pontianak. Data collection tools used interviews and TEAP user questionnaires then analyzed with the formula from Khabibah. PHP-based CBT profile in the form of a web that can be accessed online and integrated with multiple-choice item analysis. This study found that TEAP requires a system that can automatically be correcting, storing test results, analysing test results and distributing test certificates. The results showed that the effectiveness level of the respondents' opinion of the test participants with a percentage score of 77% in good category and from the opinion of respondents who implement TEAP is very effective and can analyze the level of difficulty, difference power and distractor analysis properly and quickly. This illustrates that PHP-based CBT is suitable for the TEAP program.